Avaliação Tecnológica e Aproveitamento dos Granitos e Sienitos da Região de Encruzilhada do Sul e Cachoeira do Sul, RS - Brasil - PHILIPP, RUY PAULO; SCOPEL, REJANE MARIA (Pesquisas em Geociências, 2001)
The areas of Encruzilhada do Sul and southern part of Cachoeira do Sul are the main producers of ornamental rocks in the Rio Grande do Sul State, south Brazil. Granite and syenitic rocks are exploited in this region, being consumed by the national market and exported for countries such as Japan, Italy, Germany and United States. In spite of long tradition in the extraction of ornamental rocks, the knowledge about their quality is almost totally empiric. This work presents the first results of laboratory tests for the technological characterization of five types of granites and two types of syenites in the studied area. The studies involved petrography, determination of physicals indexes, impact resistance, flexural resistance, abrasive waste (AMSLER), thermal dilatation coefficient and brightness. The selected samples also exhibited with the range of values found for the granites and syenites extracted in others states of Brazil. The results of the technological characterization tests assure the quality of granites and syenites extracted in Rio Grande do Sul, stimulating the investments in an activity of crescent economic importance.